2013
DOI: 10.1002/stem.1328
|View full text |Cite
|
Sign up to set email alerts
|

IGF1 Receptor Signaling Regulates Adaptive Radioprotection in Glioma Stem Cells

Abstract: Cancer stem cells (CSCs) play an important role in disease recurrence after radiation treatment as a result of intrinsic properties such as high DNA repair capability and antioxidative capacity. It is unclear, however, how CSCs further adapt to escape the toxicity of the repeated irradiation regimens used in clinical practice. Here, we have exposed a population of murine glioma stem cells (GSCs) to fractionated radiation in order to investigate the associated adaptive changes, with the ultimate goal of identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 59 publications
2
103
0
7
Order By: Relevance
“…The molecular phenotype of each cell is further altered by its unique position relative to other cells and local environment. Hypoxia (52), vascular niche for maintaining stemness (53,54), and secreted factors produced by other tumoral or stromal cells all influence the molecular phenotypes of tumor cells (55)(56)(57)). Heterogeneity at the cellular level adds another layer of complexity ( Figure 1C).…”
Section: The Process Of Tumor Recurrence In Gbmmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular phenotype of each cell is further altered by its unique position relative to other cells and local environment. Hypoxia (52), vascular niche for maintaining stemness (53,54), and secreted factors produced by other tumoral or stromal cells all influence the molecular phenotypes of tumor cells (55)(56)(57)). Heterogeneity at the cellular level adds another layer of complexity ( Figure 1C).…”
Section: The Process Of Tumor Recurrence In Gbmmentioning
confidence: 99%
“…GSCs can overcome the damage induced by chemotherapy and radiotherapy not only through innate properties (e.g., genetic heterogeneity), but also through adaptive resistance pathways (20,55,63). How well studies that are based on known cell surface markers represent GSC populations and behavior is being debated (58,59).…”
Section: Glioma Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the IGF-IR pathway appears to be involved in glioma stem cells' ability to adapt to repeated radiation, leading to radio-resistant cells. However, radio-resistant tumors treated with IGF-IR inhibitors have resulted in a significant increase in radiosensitivity [83,84] . It has been reported that in an in vivo model, the invasion and proliferation of glioblastomas are significantly reduced by blocking IGF-IR, while showing an increase in apoptosis and a reduction in intratumoral vascularization at the same time [85,86] .…”
Section: Insulin-like Growth Factor-i (Igf-i)mentioning
confidence: 99%
“…By doing so, NVP-BEZ235 potentiates the damage caused by ionizing radiation in glioma cells. 42,144 Some of the other targets that reportedly increase the radiosensitivity of CSCs include polo-like kinase 1, 49 cyclin-dependent kinase 6, 147 insulin-like growth factor-1 receptor, 103 DNA binding protein-1, 47 and miR-210.…”
mentioning
confidence: 99%